Blended Approach to Physics Problem-Solving Using Conventional and Virtual Labs: A Survey of Student’s Perception - Mamta Pal; Rinki (Studies in Learning and Teaching, 2022)
Physics education entails rigorous problem-solving. But physics is full of abstraction and mathematical representations, which are hard to visualize. Hence, understanding the problems requires constant lab activities essential to physics problem-solving. But due to limited equipment and limited periods of usage in conventional labs, virtual labs are an alternative with their own set of limitations. So, a blend of the two virtual and conventional labs is a better option for problem-solving. A mixed-method approach was adopted to know the perception of higher secondary students towards this blended approach. For this, 150 CBSE board higher secondary students of science stream selected using convenient sampling from Lucknow were surveyed using a Likert-type perception scale comprising 15 items followed by an unstructured interview to know the preferred mode for physics problem-solving. The data so obtained were expressed in percentages. The study revealed that most students agreed with the overall perceived benefits of using conventional and virtual labs separately. But due to the inherent problems of these labs separately, students perceived the benefits offered by the blend of conventional and virtual labs in physics problem-solving more than using them separately. A blend of conventional and virtual labs should be used more often.